Re-use of Building Products in the Netherlands - Loriane Icibaci (A+BE: Architecture and the Built Environment)
Over the years, the consumption of materials for construction exceeded more than half of the total materials consumed in the Netherlands, and construction waste exceeded the volume of solid waste produced by households. Since the introduction of the "Ladder van Lansink" (in the 1970’s) and the further development of the European Waste Framework Directives followed by the Circular Economy concept, waste prevention has been considered a priority measure. Whereas the goals to improve waste management towards waste-to-resource and waste elimination evolved from guidelines to political action (throughout the EU), reuse of products remained a less implicit strategy. The reuse of building products is an ancient practice; nonetheless, limited information is available regarding the aspects involved in the existing process. Reuse of building products has seen limited regulatory changes and remained a vague procedure within the resource efficiency discourse in the Netherlands.